Język i kultura - zagadnienia teoretyczno-prawne w pracach Bronisława Wróblewskiego: [Language and culture - theoretical and legal problems in Bronis ław Wróblewski works] (Studia Prawnicze / The Legal Studies, 1983)
In Bronisław Wróblewski's works special attention should be paid to some important and to-date problems connected with legal culture, legal language, and lawyers' language.B. Wróblewski is interested in the problems of law as a phenomenon of culture. Starting from the analysis of cultural behaviour B. Wróblewski analyses relations between values and his opinions can be interpreted as a cognitivist or non-cognitivist point of view. On the basis of a very broad analysis of legal texts B. Wróblewski reconstructs a number of attitudes of lawyers and discerns two basic types of legislators. The attitude of legislator is characterized by his attitude to the idea of order. The author compares those concepts with the opinions of G. Radbruch and C. Cossio by contrasting them from the point of view of philosophical and legal conceptions and by showing a common element, namely the relation of law to tangens of human behaviour. In connection with the problems of values the author relates B. Wróblewski's opinions on legal positivism as a methodology, as a theory of law, and as an ideology.B. Wróblewski was the first in the Polish literature to consider the problems of languages connected with law. He followed the directive semantics by K. Ajdukiewicz and linguistics of those times. The author discusses differentiations between legal and lawyers' language, their characteristics from the point of view of criteria, and analyses B. Wróblewski's opinions from the point of view of the later logical and linguistic research.